The Story of the Tanzania Parliament - Msekwa, Pius (Dar es Salaam, 2012)
This book presents a variety of materials related to the internal workings of the Tanzania parliament, by citing actual examples of what actually happened in relation to the procedures and activities taking place inside the four walls of that Institution. But beyond that, and perhaps more refreshingly, it presents this material in a historical setting, outlining the changes and developments made in respect of this institution starting from the time of independence, through the period of the One-party political system; to the time of its smooth transition to the multi-party political system; and its modified operations after the transition. The book also contains two special chapters which can be regarded as the memoirs of the author.
Keywords: Tanzanian Parliament